Conservation Subdivision: Design Phase – Wildlife-friendly Transportation Network - Mark Hostetler; Michael Moulton (EDIS, 2010)
WEC280, a 5-page illustrated fact sheet by Mark Hostetler and Michael Moulton, discusses road designs and placement strategies that will minimize impacts on local wildlife populations and enhance wildlife movement. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, May 2010.